Managing High Conservation Value and High Carbon Stock Areas in Coffee Landscapes of Mandailing Natal - Adi, Bambang Tri Sasongko; Putra, Surahman; Sari, Ratna Kusuma; Dewantara, Bonie; Suryaningtyas, Puspita (Jurnal Locus Penelitian dan Pengabdian, 2025)
The conflict between agricultural expansion and biodiversity conservation has become a global challenge, with coffee plantations contributing to 2.3 million hectares of deforestation over the past decade, particularly in tropical forest areas with high conservation value. This article explores the integration of High Conservation Value (HCV) and High Carbon Stock (HCS) safeguards within coffee-producing landscapes in Mandailing Natal District, North Sumatra. Using data from the 2023 HCV-HCS assessment, it identifies spatial overlaps between ecologically critical areas and smallholder coffee plantations, highlighting regulatory gaps that facilitate environmental degradation. This research employs a multi-method approach, combining geospatial analysis, a comprehensive regulatory review, and participatory institutional mapping, to generate innovative and integrated policy recommendations. The brief advocates for updating spatial plans, issuing local regulations, providing technical guidance, and establishing farmer incentives to support conservation-aligned coffee production. The anticipated benefits of this research include increased farmer income through sustainable certification, improved government policy effectiveness in landscape management, and the conservation of high-value ecosystems for future generations.